Problematika Materi Zakat dan Pemberdayaannya - Maryani Maryani (Fakultas Syariah Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, Indonesia, 2011)
The entire property is derived from a good source and obtained a good way, compulsory removed the zakah, when reached of nisab.zakah given to mustahiq as specified role in Al-Taubah Verse 60, pursuant to the priority. Generally the verse can accommodate all types of property about liability issues zakah. Details of the names of the zakah, which is mentioned in the hadith is not meant to limit the material zakah, but in accordance with trh realities of production at the time. Zakah and taxes are two different obligation although there are similarities to the common good, but from the points of substance, source, goal and objectives, there is a different. For that taxes liability can not replace the obligation of zakah.